Growth Performance of Daphnia sp. Cultured in Different Concentration of Rice Washing Water - Agung, Lukman Anugrah; Herjayanto, Muh.; Solahudin, Edo Ahmad; Ujianti, Rizky Muliani Dwi (Universitas PGRI Semarang, 2020)
Abstract. This study aimed to investigate the effect of the administration of rice washing water in culture medium on the growth performance of Daphnia sp. This research using three different doses of rice washing water i.e 1 mL/L, 3mL/L, and 5 mL/L. Daphnia sp. was cultured with an initial density of 20 ind/L. Observed parameters include growth parameters (population density, size and specific growth rate) and water quality. This result showed that a concentration of 3 mL/L created the highest population of Daphnia sp. density about 620Â±20 ind/L, number small size (young stage) 81.2%, and the highest specific growth rate about 56.68Â±0.55%. The water quality content ofÂ DO, temperature and pH during this study were in the good range of Daphnia sp. life and reproduction. The research has a conclusion that rice washing water can be used to nutritional sources of Daphnia sp. In the future, it is necessary to make further observations about the reproductive performance of Daphnia sp, given rice washing water through clone culture.Keywords: Live food, Population density, Rice washing water, Size of Daphnia sp., Specific growth rate